Reducing sitting at work: process evaluation of the SMArT Work (Stand More At Work) intervention - Stuart Biddle; Sophie E O’Connell; Melanie J Davies; David Dunstan; Charlotte Edwardson; Dale Esliger; Laura J Gray; Thomas Yates; Fehmidah Munir (2020)
Background: Office-based workers accumulate high amounts of sitting time. Stand More At Work (SMArT Work) aimed to reduce occupational sitting time and a cluster randomised controlled trial demonstrated it was successful in achieving this aim. The purpose of this paper is to present the process evaluation of the SMArT Work intervention.Methods: Questionnaire data were collected from intervention participants at 6 months (n = 58) and 12 months (n = 55). Questionnaires sought feedback on the different components of the intervention (education, height-adjustable desk, Darma cushion, behaviour feedback, progress chats (coaching) with research team, action planning/goal setting diary) and experiences of evaluation measures. Control participants (n = 37) were asked via questionnaire at 12-month follow-up about the impact of the study on their behaviour and any lifestyle changes made during the study. Participants from both arms were invited to focus groups to gain a deeper understanding of their experiences on completion of 12-month follow-up.Results: Focus group and questionnaire data showed a positive attitude towards the height-adjustable workstation with a high proportion of participants using it every day (62%). Most participants (92%) felt the education seminar increased their awareness of the health consequences of too much sitting and motivated them to change their behaviour. Receiving feedback on their sitting time and support from the research team also encouraged behaviour change. The Darma cushion and action planning/goal setting diary were seen to be less helpful for behaviour change. Benefits experienced included fewer aches and pains, improved cognitive functioning, increased productivity, more energy and positive feelings about general health.Conclusions: Key elements of the programme identified as facilitating behaviour change were the educational seminar, the height-adjustable workstation, behavioural feedback and regular contact with research staff through regular progress chats.Trial registration: ISRCTN: ISRCTN10967042. Registered on 2 February 2015.